Local government as a form of social solidarity (Journal of actual problems of jurisprudence, 2019)
Historical forms of socialization and solidarity of the population of different countries, nations, regional populationcan be monotonous. One of these forms of social solidarity are the local authorities, many of the crucial issues of localimportance. Historically, this form existed among the ancient Kyrgyz people and the same form is preserved by theConstitution and now needs the support of the state. Kyrgyz identity model of local self-government has its reasonsrelated to national traditions, customs Kyrgyz and Kazakhs trust, mutual respect, democratic relations, etc.Key words: local government, social solidarity, the government, the legal self-fulfillment, social management, statehood.